Viga de concreto armado utilizando garrafas pet - SOBRAL, Alexandre Salomão Barile (2016)
The use of PET bottle in civil construction became very common, considering that can be used in walls construction, making of tiles, among others. There are already many studies where it was found the use of PET bottle as component of structure or of construction itself and show satisfactory results. The optimization at execution of pieces in reinforced concrete aiming ensure reduction of own weight, as well as, reduction of materials employed and consequently the reduction of the cost, it’s a case requires a attention at civil construction area. The hollow or empty beams are a good alternative for this optimization, so in this study it were tested at Civil Engineering Laboratory of Federal University of Pará 4 beams with section of (120 x 400) mm² and 2200 mm of length, being 1 massive for reference and 3 of them with empty area: the first (Beam B1) using one line of PET bottle of 600 ml lying, the second (Beam B2) with two lines of PET bottle lying (one bottle over the other) and the third (Beam B3) with three lines of bottles lying (also one over the other) all disposed longitudinally in the beam. It was studied the presence of armor of shear and the model test Stuttgart and was performed the comparison of load capacity between the tested beams. Hollow beams showed behavior near to reference beam. There was a reduction of volume and consequently of weight between the beams BR and B3 of nearly 15,3% and a loss of resistance to shear between the same beams of nearly 26,3%. The tests results were compared with the NBR 6118 (2014) recommendations and it was found a nearness between the results.